The pillars of land plants: new insights into stem development. (October 2018) - Serrano-Mislata, Antonio; Sablowski, Robert
Highlights: New image analysis revealed 3D growth patterns in the rib zone of the shoot meristem. Organ boundary genes emerged as an important control point in early stem growth. Stem elongation correlates with changes in pectin and its interaction with cellulose. Stem growth requires coordination across tissues with different mechanical properties. Abstract : In spite of its central importance in evolution, plant architecture and crop improvement, stem development remains poorly understood relative to other plant organs. Here, we summarise current knowledge of stem ontogenesis and its regulation, including insights from new image analysis and biophysical approaches. The stem initiates in the rib zone (RZ) of the shoot apical meristem, under transcriptional control by DELLA and BLH proteins. Links have emerged between these regulators and cell proliferation, patterning and oriented growth in the RZ. During subsequent internode elongation, cell wall properties and mechanics have been analysed in detail, revealing pectin modification as a prominent control point. Recent work has also highlighted signalling to coordinate growth of stem tissues with different mechanical properties.